Survival Outcomes of U.S. Patients with CMML: A Two-Decade Analysis from the SEER Database - Ayrton Bangolo; Behzad Amoozgar; Abhishek Thapa; Wardah Bajwa; Vignesh K. Nagesh; Yaryna Nyzhnyk; Rakshanda Banu; Tirth Bhavsar; Lili Zhang; Olga Velichko; Challa Mani Shankar Reddy; Edwina Essuman; et al. (Medical Sciences)
Background: Chronic Myelomonocytic Leukemia (CMML) is a rare and aggressive form of leukemia with characteristics of both myeloproliferative neoplasms (MPNs) and myelodysplastic syndromes (MDSs). This study aims to explore the clinical features, survival outcomes, and prognostic factors in CMML patients over the past 20 years using a large sample. Methods: The study data from 4124 patients diagnosed with CMML between 2000 and 2017 were sourced from the SEER database. Demographic and clinical characteristics, along with overall and cancer-specific mortality, were examined. Factors with a p-value < 0.01 in univariate Cox regression were included in the multivariate Cox model to identify independent prognostic factors, with hazard ratios (HRs) greater than one indicating adverse outcomes. Results: The majority of the cohort were male (61.57%), and most diagnoses occurred between ages 60–79 (55.16%), with a small percentage under 40 (1.41%). Non-Hispanic whites represented the largest racial group (79.03%). Multivariate analysis showed higher mortality in males, those aged 80+, residents in metropolitan areas with populations between 250,000 and 1 million, single or widowed individuals, and those who underwent chemotherapy. Conversely, lower mortality was associated with an annual income of $75,000+. Conclusions: CMML remains a rare and highly aggressive hematologic disorder. This U.S.-based retrospective cohort study identified male gender, advanced age, single or widowed status, and chemotherapy as independent poor prognostic factors. While it is expected that older patients and those requiring chemotherapy would have a poorer prognosis, the higher mortality risk in single or widowed patients, as well as males, warrants further investigation. The early involvement of family and community support may help reduce mortality in these groups, suggesting a need for larger prospective studies to explore these associations further.